2016
DOI: 10.1515/limre-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of rotifer communities in lakes of the Suwalki Landscape Park

Abstract: Studies of summer rotifer fauna of 11 shallow and 6 deep lakes of the Suwałki Landscape Park were conducted in an aim to assess the role of lake depth and biotic and abiotic factors in determining the diversity of rotifer communities in lakes undergoing a natural rate of eutrophication not accelerated by anthropopression. Some differences were observed when the group of shallow lakes was compared with that of deep lakes. The former were more differentiated as regards a list of rotifer species, partly due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…They suggested food competition and adverse conditions as possible causes for a decrease in species number. Onandia et al [36] and Ejsmont-Karabins et al [179] also reported a decrease in planktonspecies number at higher trophic levels, which Ejsmont-Karabins et al [179] explained by a left-truncated humpback relation. We observed negative correlations for species richness and Shannon diversity with phosphorus compounds but lack analytical detail for TP to examine the relationship at lower concentrations, whereas a linear decline occurred with ortho-P. Other variables associated with productivity (chl a, pGOP, oxygen saturation) were, however, unrelated-unimodal nor linear-to diversity metrics, making control by food resources less likely.…”
Section: Discussionmentioning
confidence: 96%
“…They suggested food competition and adverse conditions as possible causes for a decrease in species number. Onandia et al [36] and Ejsmont-Karabins et al [179] also reported a decrease in planktonspecies number at higher trophic levels, which Ejsmont-Karabins et al [179] explained by a left-truncated humpback relation. We observed negative correlations for species richness and Shannon diversity with phosphorus compounds but lack analytical detail for TP to examine the relationship at lower concentrations, whereas a linear decline occurred with ortho-P. Other variables associated with productivity (chl a, pGOP, oxygen saturation) were, however, unrelated-unimodal nor linear-to diversity metrics, making control by food resources less likely.…”
Section: Discussionmentioning
confidence: 96%
“…Simultaneously, data from 2004 and 2013 indicated a significant increase in the numerical share of the tecta form of this species in its overall abundance. Keratella cochlearis is a cosmopolitan, eurytopic species [43] that occurs commonly in various types of lakes, including in the northern hemisphere both in America [44] and in Europe [45][46][47]. Keratella cochlearis exhibits a strong dependence on phosphorous availability [27].…”
Section: Discussionmentioning
confidence: 99%
“…Trophic state is one of the most important characteristics to classify nutritional load of an aquatic ecosystem (Jekatierynczuk-Rudczyk et al, 2014; Dembowska et al, 2015;Ejsmont-Karabin et al, 2016;Wen et al, 2017;Smaoune et al, 2020). Various environmental factors are applied to measure the trophic status of a lake.…”
Section: Introductionmentioning
confidence: 99%